Prevalence of multidrug-resistant bacteria in a public hospital located in the highlands of Peru - Quispe-Pari, Franck (2023)
Introduction. Antibiotic resistance is one of the greatest threats to global health. One of the strategies for its control is microbiological surveillance. Objective. To describe the variation of the prevalence of multidrugresistant strains (MDR) of the most frequently isolated bacteria in clinical samples of patients treated at a tertiary care hospital in a high-altitude city in Perú and the factors associated with its isolation. Also, to assess the prevalence of other resistance phenotypes. Results. The general prevalence of MDR strains was 74,1%, observing a downward trend in the annual prevalence of MDR strains in five of the nine bacteria included. The factors associated with MDR strains corresponded to those previously described: male sex, age over 75 years, and hospitalization in intensive care services. In addition, an increase in the annual prevalence of other resistance mechanisms was evidenced. Conclusions. A high prevalence of MDR strains was found in all the bacteria evaluated, associated with previously described factors.